2018
DOI: 10.1007/s12551-018-0399-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water and ionic liquids on biomolecules

Abstract: The remarkable progress in the field of ionic liquids (ILs) in the last two decades has involved investigations on different aspects of ILs in various conditions. The nontoxic and biocompatible nature of ILs makes them a suitable substance for the storage and application of biomolecules. In this regard, the aqueous IL solutions have attracted a large number of studies to comprehend the role of water in modulating various properties of biomolecules. Here, we review some of the recent studies on aqueous ILs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 132 publications
(151 reference statements)
0
26
0
1
Order By: Relevance
“…Another important property of ILs is their specific interaction with DNAs. In general, five interactions play major roles in determining the stabilities and structures of DNAs: hydrogen bonding, base stacking, conformational entropy, hydration, and cation binding (Saenger 1984). The interactions of hydration and cation binding depend upon surrounding conditions (Nakano et al 2014c; Saha and Mukherjee 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important property of ILs is their specific interaction with DNAs. In general, five interactions play major roles in determining the stabilities and structures of DNAs: hydrogen bonding, base stacking, conformational entropy, hydration, and cation binding (Saenger 1984). The interactions of hydration and cation binding depend upon surrounding conditions (Nakano et al 2014c; Saha and Mukherjee 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acids (DNA and RNA) contain a negatively charged sugar-phosphate backbone, and their bases possess aromatic rings, which have the donor and acceptor sites used for hydrogen bonding (Fig. 1a) (Saenger 1984). The DNA forms a duplex in cells via base pair formation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The rising interest in aqueous ILs can be mainly rationalized in terms of a broad impact on several fields of research, ranging from food science and pharmaceutical applications to protein structure crystallography (Patel et al 2014a). Besides long-time storage (Byrne and Angell 2008) and stimulated biocatalytic activities in neat ILs (van Rantwijk and Sheldon 2007;Zhao 2015b; Benedetto and Ballone 2015; Egorova et al 2017), aqueous ILs have shown their benefits as promising solutions to systematically stabilize or destabilize protein and enzyme structures (Kumar and Venkatesu 2013;Patel et al 2014a;Benedetto and Ballone 2015;Egorova et al 2017;Constantinescu et al 2007;Weingärtner et al 2012;Zhao 2015b;Schröder 2017;Smiatek 2017;Saha and Mukherjee 2018). Often studied species are aqueous dialkylimidazolium based aprotic ILs (Constantinescu et al 2007;Weingärtner et al 2012;Zhao 2015b;Senske et al 2016;Schröder 2017;Smiatek 2017), in addition to protic or aminoacid based ILs (Baker et al 2004;Fujita et al 2005;Fukumoto et al 2005;Constantinescu et al 2007;Mann et al 2009;Fujita and Ohno 2010;Weingärtner et al 2012;Patel et al 2014b;Senske et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, nucleic acids are popular building blocks for the design and synthesis of nanomaterials, owing to special base pairing interactions. Unique interactions between nucleic acid and ILs make remarkable differences compared with aqueous conditions [ 3 , 4 ]. A representative IL, choline dihydrogen phosphate (choline dhp), ensures long-term stability of biomolecules, such as proteins and DNA, suggesting that choline dhp is a good solvent for the development of nanomaterials [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%